From mother orientation to family orientation : possibilites of transformation antenatal to postnatal services into a widened focus - Kristin Adamaszek (2007)
The objective of the Master Thesis of Public Health at hand is to develop a feasible concept for a family oriented approach of antenatal and postnatal services in Germany. Starting point is a description of current defiance of antenatal and postnatal period in Germany and the focus of the service as mainly being mother oriented and risk oriented. The thesis presents differenct scientific approaches offering theoretical base for a widened service, Systemc theory, the concept of Family Medicine, Antonovskys Salutogenesis and Resilience research.